(untitled) (World Bulletin of Public Health, 2026)
In the article "Treatment of patients with peptic ulcer of the stomach and duodenum in a polyclinic" reports on the results of outpatient treatment of patients with peptic ulcer using the original method proposed by them - endoscopic autohemoapplication (EAGA) of ulcers.